ANALISIS PERBANDINGAN CITRA MEREK PRODUK KOSMETIK WARDAH DENGAN KOSMETIK LA TULIPE DI KOTA BIMA - Suryani Any 02; Is Munandar (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
Cosmetics are indeed not far from women, and most of them really need make-up such as foundation, powder, lipstick, blouse, eye liner, mascara and so on. Currently the impact of the development of cosmetics is mushrooming, therefore the cosmetics industry must be able to maintain a good image in the eyes of the public. The purpose of this study was to determine the difference in brand image between Wardah cosmetic products and La Tulipe cosmetics in Bima City. In this study, the method used is comparative research which describes the state of the research object, especially the brand image of Wardah and La Tulipe cosmetic products. The sample used is 50 respondents who use cosmetics wardah and 50 respondents who use cosmetics La Tulipe. The data analysis techniques used were validity test, reliability test, and different test of independent samples test. The research result is a probability value or sig. (2-tailed) 0.011 <0.05, then H0 is rejected and Ha is accepted, which means that a significant difference was found in the brand image between Wardah cosmetic products and La Tulipe cosmetic products in Bima City.